Analysis of accounting records and preparation of financial statements on MSME profits in the Ketanggungan District - Dwi Harini; Roni Roni; Ari Kristiana; Nur Khojin; Akbar Nuur Purnama Darma Wahana (Enrichment : Journal of Management, 2023)
Administrative documents are very important when starting a business. One of them is in the form of documents and financial statements of profit and loss. However, many SMEs have not prepared adequate financial statements, seemingly very simple. One way of financial management by compiling financial statements provides information, reports on financial income and expenses. This study aims to analyze accounting records and preparation of financial statements on profits for Micro, Small and Medium Enterprises (MSMEs) in Profit Regency in the 2022 period. The sample used was 108 respondents. Primary data is obtained from the results of filling out the questionnaire of business actors. The method of data collection is carried out with documentation and literature studies. The data analysis used is multiple linear regression analysis. The results showed that accounting records do not affect profits, financial arrangements affect profits, while simultaneously accounting records and profits affect the preparation of financial statements. Based on these results, it can be stated that accounting records and the preparation of financial statements are able to minimize the occurrence of miscalculations and the information produced will be accurate for external parties and the interested public.